2021
DOI: 10.1155/2021/3291762
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effect of Tumor Microenvironment and Angiogenesis on Clinical Outcomes of Primary Central Nervous System Lymphoma

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare lymphoma, and the disease course is often aggressive with poor prognosis outcomes. PCNSL undergoes germinal center reactions and impairs B-cell maturation. However, angiogenesis is also involved in the tumorigenesis and progression of PCNSL. This study investigated the effects of the tumor microenvironment and angiogenesis-associated genomic alterations on the outcomes of PCNSL. The analysis also evaluated the influence of treatment modality and timing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Primary CNS lymphomas (PCNSL) are a type of extranodal non-Hodgkin's lymphoma, accounting for less than 1% of non-Hodgkin's lymphomas. Of these PCNSLs, diffuse large cell B-cell lymphoma of the CNS is the most common histologically defined tumor (Wang et al, 2021). PCNSL typically forms either single or multiple hypercellular, diffusely growing lesions (Krebs et al, 2021).…”
Section: Brain Lymphomamentioning
confidence: 99%
“…Primary CNS lymphomas (PCNSL) are a type of extranodal non-Hodgkin's lymphoma, accounting for less than 1% of non-Hodgkin's lymphomas. Of these PCNSLs, diffuse large cell B-cell lymphoma of the CNS is the most common histologically defined tumor (Wang et al, 2021). PCNSL typically forms either single or multiple hypercellular, diffusely growing lesions (Krebs et al, 2021).…”
Section: Brain Lymphomamentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%